2001
DOI: 10.1074/jbc.m104685200
|View full text |Cite
|
Sign up to set email alerts
|

Human Transforming Growth Factor-β Activates a Receptor Serine/Threonine Kinase from the Intravascular ParasiteSchistosoma mansoni

Abstract: The biology of the helminth parasite Schistosoma mansoni is closely integrated with that of its mammalian host. SmRK1, a divergent type I transforming growth factor-␤ (TGF-␤) receptor of unknown ligand specificity, was previously identified as a candidate for a receptor that allows schistosomes to respond to hostderived growth factors. The TGF-␤ family includes activin, bone morphogenetic proteins (BMPs), and TGF-␤, all of which can play crucial roles in metazoan development. The downstream signaling protein o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 34 publications
(45 reference statements)
1
46
0
1
Order By: Relevance
“…These findings are mirrored in the human clinical setting, where studies of HIVpositive patients in regions endemic for S. mansoni revealed that fecal egg counts, but not infection intensity, were negatively correlated with CD4 + T cell counts [23]. Further supporting the coevolution of S. mansoni with the mammalian immune system, evidence exists that adult worms can sense the human regulatory cytokine, transforming growth factor beta (TGF-β), and that stimulation with TGF-β induces expression of genes linked to sexual maturation and malefemale interaction and may modulate embryonic development [24][25][26][27]. S. mansoni has thus evolved not only to detect mediators of host immunity, but also to use these signals in its own program of maturation and reproduction.…”
Section: Abbreviationsmentioning
confidence: 99%
“…These findings are mirrored in the human clinical setting, where studies of HIVpositive patients in regions endemic for S. mansoni revealed that fecal egg counts, but not infection intensity, were negatively correlated with CD4 + T cell counts [23]. Further supporting the coevolution of S. mansoni with the mammalian immune system, evidence exists that adult worms can sense the human regulatory cytokine, transforming growth factor beta (TGF-β), and that stimulation with TGF-β induces expression of genes linked to sexual maturation and malefemale interaction and may modulate embryonic development [24][25][26][27]. S. mansoni has thus evolved not only to detect mediators of host immunity, but also to use these signals in its own program of maturation and reproduction.…”
Section: Abbreviationsmentioning
confidence: 99%
“…1) and shown to be expressed at the surface of the parasite following its entry into the mammalian host [13]. Using a heterologous expression system, SmTbR1 was shown to interact with human TbRII and to activate Smad2 signalling molecules in response to human TGF-b [14]. Two R-Smads (SmSmad1 and SmSmad2) as well as a Co-Smad (SmSmad4) have been identified as downstream partners of SmTbR1 [15][16][17].…”
Section: Conserved Tgf-b Signalling In Parasitic Helminthsmentioning
confidence: 99%
“…Both Smads (SmSmad1 and SmSmad2) and SmRK1 are found in the same developmental stages (lung stage and adult parasites). SmSmad2 interacts with SmRK1, while SmSmad4 interacts with SmSmad1 and SmSmad2, besides phosphorylating Erk1/2 (kinase regulated by extracellular signal) (Beall et al 2000, Beall & Pearce 2001, Osman et al 2001. FKBP12 influences a variety of signal transduction pathways that regulate cell division, differentiation, and ion homeostasis.…”
Section: S Mansoni Proteins Involved In Signal Transductionmentioning
confidence: 99%